2016
DOI: 10.1371/journal.pone.0149246
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Central Retinal Sensitivity for Prediction of Visual Acuity after Intravitreal Bevacizumb in Eyes with Macular Edema Associated with Branch Retinal Vein Occlusion

Abstract: ObjectiveTo determine whether the baseline retinal sensitivity can predict the best-corrected visual acuity (BCVA) at 1 month after intravitreal bevacizumab (IVB) in eyes with macular edema (ME) associated with a branch retinal vein occlusion (BRVO).Subjects and MethodsWe evaluated 16 eyes of 16 patients who had ME associated with a BRVO. The mean ± standard deviation age was 69.1 ± 8.9 years, and all had a single IVB injection. The BCVA, central macular thickness (CMT), integrity of the ellipsoid zone (EZ) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[ 30 ] These examinations provide different aspects of visual function, and MP has the advantage of assessing additional information in the central area of 10° around the fovea quantitatively. [ 29 , 31 , 32 ] In addition, follow-up examinations have been useful to evaluate the effectiveness of treatments. [ 33 , 34 ] Here, we showed improved of RS in DME patients with comparatively good VA, although the BCVA did not improve significantly for patients with a BCVA >0.7.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] These examinations provide different aspects of visual function, and MP has the advantage of assessing additional information in the central area of 10° around the fovea quantitatively. [ 29 , 31 , 32 ] In addition, follow-up examinations have been useful to evaluate the effectiveness of treatments. [ 33 , 34 ] Here, we showed improved of RS in DME patients with comparatively good VA, although the BCVA did not improve significantly for patients with a BCVA >0.7.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies which suggested the usefulness of the anti-VEGF therapy in eyes with BVO with ME [5][6][7][8][15][16][17][18][19]. For instance, Mylonas et al have reported that BCVA improved significantly at 3 months and 12 months after the anti-VEGF therapy in patients with BVO [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al [8] suggested retinal sensitivity using MAIA at 1 day after the intravitreal bevacizumab was correlated with BCVA at 1 month in patients with BVO. Agreeing with this report [8], our results suggested that the retinal sensitivity at 1 month is a useful predictive factor of BCVA at 3 months, which was consistent with the previous report. More specifically, as a result of model selection, the optimal model for BCVA3m included BCVAbase, ΔBCVA1m, and ΔMS1m or ΔqMS1m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of macular edema secondary to branch retinal vein occlusion has greatly improved in recent times with the introduction of a therapy based on intravitreal injection of antivascular endothelial growth factor (VEGF) molecules and steroids [69]. Patient outcomes even with identical treatments can be vastly different due to disease, and patient heterogeneity prognostic factors for BRVO include patient age [70], baseline visual acuity and retinal thickness [51, 71, 72], early response to treatment [70], duration of macular edema [73, 74], posterior vitreous detachment [75], OCT characteristic [7678], cytokine level [34, 79], central retinal sensitivity [80], leaking capillaries and microaneurysms in the perifoveal capillary network [60, 81, 82], retinal pigment epithelium (RPE) integrity [83, 84], serious retinal detachment [85], and subretinal hemorrhage [86]. Some of these prognostic factors are still controversial.…”
Section: Treatmentmentioning
confidence: 99%